Evaluasi Aspek Teknis Peternakan Sapi Perah Rakyat di Kabupaten Karo Sumatera Utara Evaluation of Technical aspects on Smallholder Dairy Farm in Karo Regency of North Sumatera - Simamora, T.; Fuah, A. M.; Atabany, A.; Burhanuddin, Burhanuddin (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Dairy farm has strategic roles in meet the demand of foods. The development of dairy cattle encourages creation of sustainable. In North Sumatera, Karo Regency is known as one of regions with most dairy farms, but now the farms is in stagnancy status. The stagnancy was affected by genetic and environment factors, so this research is aimed to evaluating technical aspect of dairy farms based on Good Dairy Farming Practice (GFDP). The method that used in this research was survey, respondent was collected by census with respondents as total sampling. Data was analyzed with chi-square test. Result of this research showed that highest GDFP point was management aspect, with 3.05 points (good) when lowest GDFP point was dairy cattle health aspect, with 1.52 points (less good). Key word: GDFP , Karo Regency , Dairy Cattle